Phytobiotic effect of Jatropha curcas leaf powder on productivity, egg quality and blood biochemistry of laying quails - Salazar, Ivonne; Rodríguez, R.; Aroche, R.; Valdivié, M.; Martínez, Y. (Cuban Journal of Agricultural Science, 2021)
To evaluate the phytobiotic effect of Jatropha curcas leaf powder on productivity, egg quality and blood biochemistry of laying quail (Coturnix japonica), the phytochemical screening of leaves of this plant was carried out. An amount of 150 laying quails, 25 weeks old, were randomly distributed into three treatments and five repetitions per treatment for 70 days. Treatments consisted of dietary supplementation with 0, 0.5 and 1.0 % of J. curcas leaf powder. Alkaloids, coumarins, resins, anthocyanidins, saponins, free amino acids, tannins, quinones, flavonoids, and mucilages were found in the medicinal powder. The addition of 0.5 % of powder improved (P <0.05) laying intensity (1.89 %), although there were no significant changes (P> 0.05) for live weight, viability, feed intake, mass conversion and percentage of non-apt eggs. At weeks 30 and 35 of age, the experimental group with 0.5 % increased the height of the dense white (0.59 and 0.36 mm) and Haugh unit (2.82 and 2.09). The rest of egg quality indicators did not differ among treatments (P> 0.05). In blood, the addition of 0.5% reduced (P <0.05) glucose and creatinine concentration and the treatment with 1 % increased the concentration of aminotransferase aspartate, although without notable differences for the concentration of alanine aminotransferase, total cholesterol and uric acid (P > 0.05). Dietary supplementation with 0.5 % of J. curcas leaf powder is suggested in laying quail diets to improve laying, egg quality and blood chemistry. Keywords: additive, quail, productive indicator, egg quality, blood indicator